If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = 6 + 4w Solving 26 = 6 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 26 + -4w = 6 + 4w + -4w Combine like terms: 4w + -4w = 0 26 + -4w = 6 + 0 26 + -4w = 6 Add '-26' to each side of the equation. 26 + -26 + -4w = 6 + -26 Combine like terms: 26 + -26 = 0 0 + -4w = 6 + -26 -4w = 6 + -26 Combine like terms: 6 + -26 = -20 -4w = -20 Divide each side by '-4'. w = 5 Simplifying w = 5
| -8m+15+9m=-3 | | -5+5u=15 | | 7a+2a+3=30 | | 4x+9-3x=7 | | 6x+3y=160 | | 2(-4+35)= | | 3m-5=5w-7 | | 8x^6= | | 6x-19=-91 | | 3(x-7)-4(x-8)-9(x-5)=2 | | 80t^2-80t-50=0 | | -v/4=-35 | | log^6(3x+4)=2 | | 80t^2-80t+50=0 | | 11/4a-7=-1 | | 80t^2+80t+50=0 | | 24+6y=60 | | 25=-v/6 | | 5xy+2x^2+2y^2=27 | | -10x=58 | | 54=4v+14 | | (5x-2)-(3x+1)-x-60=0 | | 2/3(5-a=2 | | 3u-17=40 | | 2x+3x=3x+20 | | 6x^22-6x-72=0 | | 4a-5+3a+7-a-8a= | | (3x+9)(7x-2)=0 | | 8m(5+2m)= | | 7a+15=11a-3 | | y=0.2x^2-5x+30 | | y=0.2x^2-5Q+30 |